Zero Energy Residential Buildings Design in Hot Climate Zone - Naghibi, Seyed Arash (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Buildings consume a significant proportion of the total energy used worldwide and consequently emit masses of green gases. Therefore, energy management in the buildings plays an important role in formulating sustainable development strategies. There is a growing interest in zero energy buildings (ZEBs) in recent years. Several countries have adopted or considered establishing ZEBs as their future building energy targets to address the problems concerning the depletion of energy resources and the environmental issues. In general, ZEBs involve two design strategies. Firstly, to minimize the need for energy consumption in buildings (especially for heating and cooling) through energy efficient measures and secondly to adapt renewable energy technologies to fulfil the remaining energy needs. The aim of this thesis is to do a comprehensive investigation of design strategies in order to select proper solution applied in buildings and proposed solutions to attain Net Zero Energy Buildings (Net ZEBs) in hot climates. For the undertaken subject of this study, firstly the concept of ‘Zero Energy/Emission Building’ (ZEB) is to be analyzed in detail. For this purpose, ZEB building strategies in terms of energy production and consumption for hot climate areas have been considered. The thesis contains three chapters. The first chapter focuses on the review and analysis of main design principles, technologies and solutions. The objective is to reach an energy balance in residential building in hot climate zone by selecting the proper methods for reducing energy in terms of thermal and visual comfort and producing energy from renewable energy sources. In the third chapter the factors discussed in chapter 2 are evaluated by selecting case studies in hot and arid and hot and humid climates. Finally, chapter 3 concludes the study by comparing the reported data. The result shows similar patterns, the designer aims to minimize energy by understanding the best local passive systems and optimizing them by recent technologies such as sufficient materials and most effective insulation. Similar to the literature findings, most of the energy for the case studies is produced by solar radiation in hot climate regions. Nevertheless, attention should be paid about heat gain by radiation using proper insulation and envelope design, while Occupants of the modern buildings expect comfortable conditions combined with balance in energy consumption to reduce environmental effects as well as energy cost.

ÖZ: Binalarda harcanan enerji ve çevreye olumsuz etkisi global ölçekte kayda değer seviyededir. Dolayısıyla, binalarda enerji yönetimi stratejileri, surdürülebilir gelişim için önem taşımaktadır. Günümüzde Sıfır Enerji Bina (ZEBs) uygulamalarına olan ilgi giderek artmaktadır. Enerji kaynaklarının azalması ve yüksek enerji kullanımının çevreye olan olumsuz etkisini dikkate alan birçok ülke, bu kavramı gelecek planlarına dahil etmeye başlamıştır. Sıfır Enerji Bina (ZEBs) tasarım stratejisi temel olarak iki adımdan oluşur. Öncelikli olarak, özellikle ısısal konfor ve aydınlarma için harcanan enerjinin azaltılması hedeflenir. İkinci adımda ise, yenilenebilir enerji kullanımının bina enerji sistemine adapte edilmesine çalışılır. Bu tez kapsamında amaçlanan, sıcak iklimlerde uygulanmış tasarım stratejilerinin, seçilen örneklemlerle mukayeseli olarak karşılatırılması ve bunun sonucunda Sıfır Enerji Bina (ZEBs) tasarımı için uygun çözümler önerilmektir. Üç bölümden oluşan tez kurgusunda öncelikle, sıcak iklimlerde Sıfır Enerji Bina (ZEBs) kavramı, binalarda enerji ihtiyacı ve enerjinin etkin kullanımı açısından tüm detaylarıyla irdelenmiş, temel tasarım stratejileri, teknolojileri ve uygulamaları tanıtılmıştır. İkinci bölümde sıcak iklim bölgelerinde, konutlarda, ısısal ve görsel (ışık) konforun sağlanabilmesi için harcanan enerjinin azaltıması ve yenilenebilir enerji kaynakları kullanımı ile bina enerji sisteminin dengelenmesi için gerekli yöntemlerin tanıtılması ve tartışılması yapılmıştır. Üçüncü bölümde, ikinci bölüm kapsamında tartışılan tasarım stratejileri ışığında, seçilen bina uygulamaları tartışılmış, sonuç bölümünde ise araştırma neticesinde sıcak iklim bölgelerinde yer alan Sıfır Enerji Bina tasarım stratejileri özetlenmiştir. Tasarımcılar, sonuç olarak benzer tasarım stratejileriyle, binalarda enerji kullanımını azaltmak amacıyla yerel iklim koşullarına en uygun edilgen (passive) bina sistemlerini günümüz teknolojisine vi uygun yapım ve yalıtım malzemeleri kullanarak hedeflerine ulaşmaya çalışmaktadır. Literatür araştırmasında elde edilen bilgilere parallel olarak, tez kapsamında, sıcak iklim bölgelerinde yer alan örneklem binalarda da enerji üretimi çoğunluka güneşten sağlanmaktadır. Bununla birlikte, iç mekanda ısıl konfor koşullarının oluşması, ihtiyaç duyulan enerji miktarının azaltılması ve enerji maliyetinin düşürülmesi için, güneş ışınımlarından oluşan aşırı ısı kazancının, gerek yalıtım yapılarak, gerekse bina kabuğu tasarımında önlemler alınarak kontrol edilmesi gerekmektedir.
Master of Science in Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2016. Supervisor: Assist. Prof. Dr. Polat Hançer.
Keywords: Architecture; Architecture and energy conservation; Housing--Energy conservation--Energy consumption; Buildings--Environmental aspects; Sustainable construction; Sustainable buildings--Economic aspects; Net Zero Energy Building Design; Residential building; Renewable Energy; Energy Efficient Buildings Envelope; Passive systems; Mechanical systems consumption Energy; Low energy; Hot climate Zone